S03.1 Endothelial function in systemic lupus erythematosus patients: impact of caffeine consumption on endothelial progenitor cells survival. (27th September 2022) - Orefice, V; Ceccarelli, F; Barbati, C; Putro, E; Pirone, C; Alessandri, C; Conti, F
Abstract : Purpose: Circulating endothelial progenitor cells (EPCs) are widely demonstrated biomarkers of endothelial function. Their frequency and function varied in systemic lupus erythematosus (SLE) patients, with a significant association with subclinical atherosclerosis. 1 Caffeine, one of the most widely consumed products in the world, seems to improve endothelial cells number and EPCs migration in coronary artery disease both in mouse models and in patients. 2 The purpose of this study was to evaluate the role of caffeine intake on endothelial function in SLE patients, by assessing its effect on number and function of EPCs both ex vivo in SLE patients and in vitro in healthy donors (HD) treated with SLE sera. Methods: We performed a cross-sectional study enrolling SLE patients excluding patients with history of traditional cardiovascular risks factors. Caffeine intake was evaluated using a 7-day food frequency questionnaire. At the end of questionnaire filling circulating EPCs were detected by using a flow cytometry analysis. Subsequently, EPCs pooled from 6 HD were co-cultured with caffeine at 0.5 mM and 1 mM with and without SLE sera. After 7 days, we evaluated the cells morphology and the ability to form colonies. Moreover, we analyzed for the percentage of annexin V-positive (AV) apoptotic cells by flow cytometry analysis and for levels of autophagy and apoptotic markers LC3-II, p62 and Bcl2 by western blot. Finally, EPCs were also treated with SLE sera, alone or in combination with caffeine at 1 mM, in the presence of protease lysosomal inhibitors E64d and Pepstatin A. Results: We enrolled 31 SLE patients (F:M 30:1, median age 43 years, IQR 18; median disease duration 144 months, IQR 180). We found a EPCs median percentage of 0.03% (IQR 0.04) observing a positive correlation between caffeine intake and EPCs percentage (p=0.03, r=0.4). Moving on in vitro experiments, HD EPCs treated with SLE sera and caffeine showed an improvement in morphology and in number of EPCs-CFU in comparison with those incubated with SLE sera without caffeine (p=0.0003). Moreover, the colonies treated with SLE sera were poorly organized in comparison with HD; the addition of caffeine restored the colony structure. After treated HD-EPCs with SLE sera we observed an increase in AV positive cells and p62 values and a reduction of LC3-II and Bcl2 values; the addition of caffeine was able to significantly reduce AV positive cells and p62 values and to significantly increased LC3-II and Bcl2 values ( Figure 1A-D ), without any significant differences between caffeine 0.5 mM and 1 mM treatment. Finally, in the presence of protease inhibitors, we didn't observe any significant difference in the autophagy and apoptotic markers values, compared to condition without inhibitors. Conclusions: Our data demonstrated the ability of caffeine in increasing the number of circulating EPCs in SLE patients. Moreover in vitro experiments seem to suggest a protective role of caffeine on EPCs survival and vitality through the promotion of autophagy and the inhibition of apoptosis. References: Westerweel et al. Ann Rheum Dis 2007. Spyridopoulos et al. Art. Thromb Vasc Biol . 2008.